PENGARUH KESEIMBANGAN KEHIDUPAN-KERJA, HUBUNGAN ATASAN DAN BAWAHAN, DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA PADA KARYAWAN MILENIAL PERUSAHAAN STARTUP DI JAKARTA SELATAN - Nahda Miftah Aulia (2022)
This research is using quantitative study aimed to see whether there are influence of work-life balance, leader-member exchange, and career development on job satisfaction. This study uses millennial startup employees at south jakarta as samples. The sample used was 96 respondents, with the sampling technique using purposive sampling. In this research hypothesis, namely to know the effect either partially or simultaneously of variables independent and dependent variable, so the tests used are the coefficient of determination test, t test and f test. From the test results obtained: (1)Work-life balance has a positive and significant effect on job satisfaction (2)Leader-member exchange has a positive and significant effect on job satisfaction (3)Career development has a positive and significant effect on job satisfaction (4)Work-life balance, leader-member exchange, and career development have a simultaneous effect on job satisfaction.